IMPLEMENTASI PEMBELAJARAN SEJARAH BERBASIS MULTICULTURAL APPROACH BAGI SISWA SEKOLAH DASAR TUNA RUNGU SKH NEGERI 01 KOTA SERANG - Rikza Fauzan; Veri Setiawan; Ratih Lutfita Ningtyas (Universitas Galuh, 2026)
History education plays an important role in fostering diversity awareness, tolerance, and respect for differences. However, its implementation for deaf students faces challenges related to communication and access to learning materials. This study aims to analyze the implementation of multicultural-based history learning for deaf students at SKH Negeri 01 Kota Serang. A qualitative approach with a single case study design was employed. Data were collected through observations, interviews, and documentation, and analyzed using the Miles and Huberman interactive model. The findings reveal that the multicultural approach was implemented through visual media, sign language, multimodal communication, and the integration of local history and culture into the learning process. These strategies enhanced students’ understanding of historical content while fostering tolerance and appreciation of cultural diversity. Nevertheless, the limited availability of adaptive learning media and variations in students’ communication abilities remain significant challenges. The study highlights the importance of accessible and culturally responsive history education in supporting inclusive learning for deaf students.